Morphodynamics of Eddy-driven submarine dunes in the Queen Charlotte Sound/Tōtaranui, New Zealand - Arnaud Doré; Giovanni Coco; Helen Macdonald (Continental Shelf Research, 2026)

Quantifying overwash in a laboratory experimental analysis using bichromatic waves - Jana Echave Lezcano; Colin Whittaker; Giovanni Coco (Coastal Engineering, 2026)

Unraveling river-tide process connectivity in complex deltaic networks - Yajun Wang; Jianliang Lin; Yu Yan; Shuxian Wang; Zhenyan She; Chengyu Jin; Kairong Lin; Tongtiegang Zhao; Giovanni Coco; Huayang Cai (Journal of Hydrology, 2025)

An initial analysis of swash flow velocity patterns - Weihan Li; Yi Pan; Weiqiu Chen; Giovanni Coco (Coastal Engineering, 2025)

Rainfall overpowers tidal forcing in driving upper tidal flat erosion and channel evolution - Shang Yu; Fan Xu; Weiming Xie; Xianye Wang; Chunyan Zhu; Qing Yuan; Haisheng Yu; Zhonghao Zhao; Yijie Zhang; Zhengbing Wang; Giovanni Coco; Qing He (Geomorphology, 2025)

Laboratory observations of continuous and intermittent subharmonic edge waves - Xuelin Ding; Roland Garnier; Colin Whittaker; Pablo Blondeaux; Giovanna Vittori; Robert A. Dalrymple; Pedro Lomonaco; R.T. Guza; Giovanni Coco (Coastal Engineering, 2025)

The role of exposure on the vertical variation of mudflat sediment erodibility - Chuning Dong; Yongping Chen; Ian Townend; Yiming Wu; Zichao Guo; Qin Jiang; Giovanni Coco; Karin R. Bryan; Zeng Zhou (Marine Geology, 2025)

The stand age governs forest root: Shoot ratios across northeast China - Han Wu; Zhenggang Du; Lingyan Zhou; Guiyao Zhou; Giovanni Coco; Jing Gao; Xuhui Zhou (Agricultural and Forest Meteorology, 2025)

Evaluating five shoreline change models against 40 years of field survey data at an embayed sandy beach - Oxana Repina; Rafael C. Carvalho; Giovanni Coco; José A.Á. Antolínez; Iñaki de Santiago; Mitchell D. Harley; Camilo Jaramillo; Kristen D. Splinter; Sean Vitousek; Colin D. Woodroffe (Coastal Engineering, 2025)

Trade-offs between vegetation and sediment availability in shaping long-term tidal network morphodynamics - Yuxian Gu; Guangxuan Han; Liang Geng; Baohua Xie; Yanan Zhang; Danghan Xie; Sergio Fagherazzi; Heyue Zhang; Giovanni Coco; Zeng Zhou (Frontiers in Marine Science, 2025)
Introduction Saltmarsh introduction has been widely implemented to restore ecosystem services and promote sedimentation in tidal mudflats, yet its effects on tidal network dynamics remain hard to predict. The interplay between saltmarsh extent and sediment availability in shaping long-term mudflat morphodynamics is not fully understood. Methods We develop a two-dimensional biomorphodynamic model to examine the individual and combined influences of saltmarsh presence and sediment availability on the evolution of tidal-flat channels. Results and discussion Our results demonstrate that sediment availability controls the long-term morphological change of mudflats, while the presence of saltmarshes exerts substantial short-term alterations in mudflat evolution. During the initial phase of saltmarsh introduction, vegetation promotes the development of tidal networks, characterized by channel elongation, narrowing and deepening. However, under higher sediment supply, saltmarshes restrict sediment deposition on landward and central mudflats compared to that on unvegetated flats. Furthermore, sediment availability primarily facilitates the extension of pre-existing channels, while saltmarshes play a dual role in both generating new channels and elongating existing ones. This distinction highlights the competing mechanisms driving channel network development.

Alongshore runup variability across contrasting beach states: Insights from field observations - Ashley David Gracia-Barrera; Amaia Ruiz de Alegría-Arzaburu; Giovanni Coco; Gonzalo Simarro; Daniel Calvete (Geomorphology, 2025)

Modelling the adaptation of estuarine morphology to macrobenthic bioturbation and sea level rise - Muriel Z.M. Brückner; Giovanni Coco; Maarten G. Kleinhans (Estuarine, Coastal and Shelf Science, 2025)

Hydrodynamic conditions of Posidonia oceanica seagrass berm formation and dismantling events - Angels Fernandez-Mora; Lluıs Gomez-Pujol; Giovanni Coco; Alejandro Orfila (Science of The Total Environment, 2025)

A hybrid, genetic programming and physically-based predictor of dune geometry - Arnaud Doré; Giovanni Coco (Geomorphology, 2025)

The interaction between vegetation patchiness and tidal flows in a shortleaf seagrass meadow - Tiago D. da Silva; Julia C. Mullarney; Conrad A. Pilditch; Giovanni Coco (Limnology and Oceanography, 2024)
Seagrasses are critical coastal habitats that provide numerous ecosystem services. The inherent patchiness within meadows exerts a significant influence on the flow‐vegetation interaction, which, in turn, affects the array of services provided by these environments. We present field observations of vegetation distribution and hydrodynamic measurements within and surrounding an approximately 2 m diameter gap (bare sediment) in a fragmented seagrass meadow. We show that variability in mean flows and turbulence is correlated with meadow structure at small (O (10 0 m)) and large (O (10 2 m)) spatial scales. Our observations reveal that bare gaps within seagrass meadows lead to faster flows and lower bed elevations. Despite slower flow speeds above the dense seagrass adjacent to the gap, the rates of dissipation of turbulent energy above the vegetation are typically around an order of magnitude larger than above the bare bed. Associated with this enhanced dissipation of turbulent energy, we observed a dominance of down‐deceleration events promoting fluid exchange and mixing and driving mass flux into the canopy. Analysis of directional variograms demonstrates that the major continuity axis within NDVI (normalized difference vegetation index) imagery (used as a proxy for vegetation biomass) coincides with the major axis of flow on both gap and meadow scales. Conversely, along the axis of minor flow variance, vegetation remains dense and exhibits greater uniformity. These findings indicate a feedback mechanism between seagrass meadow patchiness and spatial structure through flow modification, which may be beneficial for plant development.

Transport and retention of sinking microplastics in a well-mixed estuary - Gaoyang Li; Zheng Chen; Melissa Bowen; Giovanni Coco (Marine Pollution Bulletin, 2024)

Polyester microfiber impacts on coastal sediment organic matter consumption - Samantha M. Ladewig; Thomas S. Bianchi; Giovanni Coco; Eliana Ferretti; Rebecca V. Gladstone-Gallagher; Jenny Hillman; Julie A. Hope; Candida Savage; Stefano Schenone; Simon F. Thrush (Marine Pollution Bulletin, 2024)

On the role of hydrodynamic and morphologic variables on neural network prediction of shoreline dynamics - Nadia Senechal; Giovanni Coco (Geomorphology, 2024)

On the projected changes in New Zealand's wave climate and its main drivers - João Albuquerque; Jose A. A. Antolínez; Fernando J. Méndez; Giovanni Coco (New Zealand Journal of Marine and Freshwater Research, 2024)
Wave climatologies from historical and projected simulations of the ACCESS1.0, MIROC5 and CNRM‐CM5 Global Circulation Models (GCM) were sourced from the Coordinated Ocean Wave Climate Project (COWCLIP) and downscaled using the SWAN wave model. Biases between GCM's historical simulations and a regional hindcast were assessed, and the two best‐performing models (ACCESS1.0, MIROC5) had their projections analysed. A general increase in wave height and period was observed along the south/west, together with a decrease in along the north/east coasts. The projected near‐term (NEA21C) period shows mostly a increase, whilst for the long‐term (END21C) period, increased and decreased are present. The areas of statistically significant changes are larger in the END21C than in the NEA21C period. The wave direction change is counter‐clockwise along the west and clockwise along the east coasts. This study is a first assessment of historical and projected GCM‐forced waves along New Zealand and the database we generated can be of great value for renewable energy research, risk assessment and the mitigation of future coastal hazards.

Observations of beach cusp morphodynamics on a composite beach - Sebastian J. Pitman; Giovanni Coco; Deirdre E. Hart; James Shulmeister (Geomorphology, 2024)

Alongshore variability in berm and sandbar migration patterns on a highly dynamic beach - Tadashi Kono-Martínez; Amaia Ruiz de Alegría-Arzaburu; Ismael Mariño-Tapia; Giovanni Coco (Geomorphology, 2023)

Retention of buoyant plastic in a well-mixed estuary due to tides, river discharge and winds - Zheng Chen; Gaoyang Li; Melissa Bowen; Giovanni Coco (Marine Pollution Bulletin, 2023)

A regional analysis of tide-surge interactions during extreme water levels in complex coastal systems of Aotearoa New Zealand - Wagner Costa; Karin R. Bryan; Scott A. Stephens; Giovanni Coco (Frontiers in Marine Science, 2023)
Tide-surge interaction (TSI) is a critical factor in assessing flooding in shallow coastal systems, particularly in estuaries and harbours. Non-linear interactions between tides and surges can occur due to the water depth and bed friction. Global investigations have been conducted to examine TSI, but its occurrence and impact on water levels in Aotearoa New Zealand (NZ) have not been extensively studied. Water level observations from 36 tide gauges across the diverse coast of NZ were analysed to determine the occurrence and location of TSI. Statistical analysis and numerical modelling were conducted on data from both inside and outside estuaries, focusing on one estuary (Manukau Harbour) to determine the impact of TSI and estuarine morphology on the co-occurrence rate of extreme events. TSI was found to occur at most sites in NZ and primarily affects the timing of the largest surges relative to high tide. There were no regional patterns associated with the tide, non-tidal residual, or skew-surge regimes. The strongest TSI occurred in inner estuarine locations and was correlated with the intertidal area. The magnitude of the TSI varied depending on the method used, ranging from -16 cm to +27 cm. Co-occurrence rates of extreme water levels outside and inside the same estuary varied from 20% to 84%, with TSI modulating the rate by affecting tidal amplification. The results highlight the importance of investing in a more extensive tide gauge network to provide longer observations in highly populated estuarine coastlines. The incorporation of TSI in flooding hazard projections would benefit from more accurate and detailed observations, particularly in estuaries with high morphological complexity. TSI occurs in most sites along the coast of NZ and has a significant impact on water levels in inner estuarine locations. TSI modulates the co-occurrence rate of extreme water levels in estuaries of NZ by affecting tidal amplification. Therefore, further investment in the tide gauge network is needed to provide more accurate observations to incorporate TSI in flooding hazard projections.

Real-world impacts of microplastic pollution on seafloor ecosystem function - Samantha M. Ladewig; Giovanni Coco; Julie A. Hope; Amanda M. Vieillard; Simon F. Thrush (Science of The Total Environment, 2023)

Wind wave footprint of tropical cyclones from satellite data - Laura Cagigal; Fernando J. Méndez; Sara O. van Vloten; Ana Rueda; Giovanni Coco (International Journal of Climatology, 2023)
Tropical cyclones are associated with extreme winds, waves, and storm surge, being among most destructive natural phenomena. Developing capability for a rapid impact estimate is crucial for coastal applications and risk preparedness. When predicting waves characteristics associated to tropical cyclones, the traditional approach involves a two‐step procedure (a) a Holland‐type wind vortex model and (b) numerical simulations using a wave generation model, using buoy and satellite measurements for validation. In this work, we take advantage of the increasing amount of remote sensing observational data and propose a new empirical model to estimate the wind wave footprint of tropical cyclones. For this purpose, we construct a dataset with over a million satellite observations of waves triggered by tropical cyclones assuming a circular shape of the TC influence area and defining composites of significant wave height as a function of representative parameters of the track characteristics like the minimum pressure, its forward velocity, and its latitude. The validation against buoy data confirms the usefulness of the model for a first and rapid estimation of the wave footprint, although an underestimation of the most extreme events is observed due to the relatively small number of observations recorded. Due to its efficiency, the model can be applied for rapid estimations of wave footprints in operational systems, reconstruction of historical or synthetic events and risk assessments.

Medium-term observations of salt marsh morphodynamics - Chuang Jin; Zheng Gong; Lei Shi; Kun Zhao; Rafael O. Tinoco; Jorge E. San Juan; Liang Geng; Giovanni Coco (Frontiers in Marine Science, 2022)
Salt marshes play a key role in attenuating wave energy and promoting sedimentation necessary to potentially adapt to sea level rise. The changes in the soil surface elevation, as a result of spatially and temporally varied sedimentation pattern, affect the hydrodynamics, marsh edge extension and so the sedimentation rate. Little attention has yet been paid to the medium-term sedim\entation under the influence of marsh extension. To fill this gap, we performed a 6-year (from 2012 to 2018) field observation to obtain the soil surface elevation of the cross-shore tidal flats in the center Jiangsu Coast (China). The salt marsh edge is extracted from remote sensing images using NVDI technique, which allows us to quantify the seaward extension of salt marshes. Results highlight that soil surface elevation in the salt marsh region varies spatially and temporally as a function of marsh topography, inundation frequency and distance to the salt marsh edge. The sedimentation rate reduces linearly shoreward as a result of increasing soil surface elevation in the marsh region. At the transition of salt marshes and bare flats, the sedimentation rate follows a parabolic relationship with the increase in distance to the salt marsh edge but decreases linearly at the more landward sites. The maximum sedimentation rate is initially located around the mean high-water level and moves towards the edge of the salt marsh as a result of marsh extension and increasing soil surface elevation. Our field observations reveal these medium-term marsh dynamics and provide a unique dataset for development, testing and validation of numerical simulations to enhance predictions of the overall evolution of tidal flats.

Challenges and Opportunities in Coastal Shoreline Prediction - Kristen D. Splinter; Giovanni Coco (Frontiers in Marine Science, 2021)
Sandy beaches comprise approximately 31% of the world's ice-free coasts. Sandy coastlines around the world are continuously adjusting in response to changing waves and water levels at both short (storm) and long (climate-driven, from El-Nino Southern Oscillation to sea level rise) timescales. Managing this critical zone requires robust, advanced tools that represent our best understanding of how to abstract and integrate coastal processes. However, this has been hindered by (1) a lack of long-term, large-scale coastal monitoring of sandy beaches and (2) a robust understanding of the key physical processes that drive shoreline change over multiple timescales. This perspectives article aims to summarize the current state of shoreline modeling at the sub-century timescale and provides an outlook on future challenges and opportunities ahead.

Historical and future storm surge around New Zealand: From the 19th century to the end of the 21st century - Laura Cagigal; Ana Rueda; Sonia Castanedo; Alba Cid; Jorge Perez; Scott A. Stephens; Giovanni Coco; Fernando J. Méndez (International Journal of Climatology, 2020)
We developed a new hindcast for storm surge at a 0.25° spatial scale for the whole New Zealand area using a statistical downscaling technique that links the mean local atmospheric conditions with the maximum storm surge levels at a daily scale. After validating the hindcast against sea level instrumental records from 17 tidal gauges around New Zealand, the same technique has been applied to obtain storm surge projections until 2,100 using different global climate models. The global climate models have been previously classified according to their ability to reproduce the past climatology in the studied area and seven models have been selected in order to explore their effect on storm surge projections. For the two representative Concentration Pathways studied, the projections indicate that the storm surge associated with the 50 years return period will increase in magnitude in the Southern areas while it will decrease in the Northern region. Even where a decreasing linear trend over the annual maxima is observed in the future time series, sporadic events of higher magnitude than the historical peaks can be.

Coastal Sea Level and Related Fields from Existing Observing Systems - Marta Marcos; Guy Wöppelmann; Andrew Matthews; Rui M. Ponte; Florence Birol; Fabrice Ardhuin; Giovanni Coco; Alvaro Santamaría-Gómez; Valerie Ballu; Laurent Testut; Don Chambers; Justin E. Stopa (Surveys in Geophysics, 2019)

The heating of substrates beneath basaltic lava flows - Sophia W. R. Tsang; Jan M. Lindsay; Giovanni Coco; Robert Wysocki; Geoffrey A. Lerner; Erika Rader; Gillian M. Turner; Ben Kennedy (Bulletin of Volcanology, 2019)

Baseline serum levels of osteopontin predict clinical response to treatment with nivolumab in patients with non-small cell lung cancer - Federico Carbone; Francesco Grossi; Aldo Bonaventura; Alessandra Vecchié; Silvia Minetti; Nicholas Bardi; Edoardo Elia; Anna Maria Ansaldo; Daniele Ferrara; Erika Rijavec; Maria Giovanna Dal Bello; Federica Biello; et al. (Clinical & Experimental Metastasis, 2019)

Climate change, biological invasions, and the shifting distribution of Mediterranean fishes: A large‐scale survey based on local ecological knowledge - Ernesto Azzurro; Valerio Sbragaglia; Jacopo Cerri; Michel Bariche; Luca Bolognini; Jamila Ben Souissi; Giulio Busoni; Salvatore Coco; Antoniadou Chryssanthi; Emanuela Fanelli; Raouia Ghanem; Joaquim Garrabou; et al. (Global Change Biology, 2019)
Climate change and biological invasions are rapidly reshuffling species distribution, restructuring the biological communities of many ecosystems worldwide. Tracking these transformations in the marine environment is crucial, but our understanding of climate change effects and invasive species dynamics is often hampered by the practical challenge of surveying large geographical areas. Here, we focus on the Mediterranean Sea, a hot spot for climate change and biological invasions to investigate recent spatiotemporal changes in fish abundances and distribution. To this end, we accessed the local ecological knowledge (LEK) of small‐scale and recreational fishers, reconstructing the dynamics of fish perceived as “new” or increasing in different fishing areas. Over 500 fishers across 95 locations and nine different countries were interviewed, and semiquantitative information on yearly changes in species abundance was collected. Overall, 75 species were mentioned by the respondents, mostly warm‐adapted species of both native and exotic origin. Respondents belonging to the same biogeographic sectors described coherent spatial and temporal patterns, and gradients along latitudinal and longitudinal axes were revealed. This information provides a more complete understanding of the shifting distribution of Mediterranean fishes and it also demonstrates that adequately structured LEK methodology might be applied successfully beyond the local scale, across national borders and jurisdictions. Acknowledging this potential through macroregional coordination could pave the way for future large‐scale aggregations of individual observations, increasing our potential for integrated monitoring and conservation planning at the regional or even global level. This might help local communities to better understand, manage, and adapt to the ongoing biotic transformations driven by climate change and biological invaders.

Marine climate variability based on weather patterns for a complicated island setting: The New Zealand case - Ana Rueda; Laura Cagigal; Jose A. A. Antolínez; Joao C. Albuquerque; Sonia Castanedo; Giovanni Coco; Fernando J. Méndez (International Journal of Climatology, 2019)
Understanding marine climate variability is important for coastal planning and marine operations. It is also particularly challenging for complicated settings (e.g., islands) and data‐poor regions. The aim of this work is to establish a relationship between daily synoptic atmospheric patterns, and wave and storm surge conditions around New Zealand waters, based on instrumental and reanalysis data. The daily predictor we developed is able to represent sea and swell wave conditions as well as storm surge variability over different temporal scales. However, when climate variability is analysed on a longer temporal period, based on the 20th century reanalysis, large inhomogeneities are found. This highlights the dangers related to assessing climate variability, especially in data‐poor regions (such as New Zealand), where inhomogeneities could be interpreted as actual changes.

A numerical study of equilibrium states in tidal network morphodynamics - Fan Xu; Giovanni Coco; Zeng Zhou; Jianfeng Tao; Changkuan Zhang (Ocean Dynamics, 2017)

Modeling the morphodynamic response of tidal embayments to sea-level rise - Barend van Maanen; Giovanni Coco; Karin R. Bryan; Carl T. Friedrichs (Ocean Dynamics, 2013)